Delegated Monitors, Large and Small: The Development of Germany's Banking System, 1800-1914 - Timothy Guinnane (Center for Economic Studies and ifo Institute (CESifo), 2001)
Banks play a greater role in the German financial system than in the UnitedStates or Britain. Germany's large universal banks are admired by those whoadvocate bank deregulation in the United States. Others admire the universalbanks for their supposed role in corporate governance and industrial finance.Many discussions distort the German banking system by over-stressing oneof several types of banks, and ignore the competition and cooperationbetween the famous universal banks and other banking groups. Tracing thehistorical development of the German banking system from the earlynineteenth century places the large universal banks in context.
Keywords: 330; universal banking; German banks; German economic history